The Diagnostic Value of Soluble ST2 in Heart Failure: A Meta-Analysis - Yang, Chaojun; Fan, Zhixing; Wu, Jinchun; Zhang, Jing; Zhang, Wei; Yang, Jian; Yang, Jun (Frontiers in Cardiovascular Medicine, 2021)
Objective: The diagnostic performance of soluble suppression of tumorigenicity (sST2) in heart failure (HF) had been investigated in multiple studies, but the results were inconsistent. This meta-analysis evaluated the diagnostic value of sST2 in HF. Methods: Pubmed, Web of Science, Embase, and Cochrane Library databases were searched until March 2021. Cohort studies or case-control studies relevant to the diagnostic value of sST2 in HF were screened, and true positive (TP), false positive (FP), false negative (FN), and true negative (TN) data were extracted for calculating sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and area under the curve (AUC). The quality of the included studies was evaluated using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS), the threshold effect was determined by calculating Spearman correlation coefficients and summary receiver operating characteristic (SROC) curve patterns, the heterogeneity was evaluated using the I2 statistic and the Galbraith radial plot, and sensitivity analysis was also performed. Deeks' test was used to assess publication bias. Results: A total of 11 studies from 10 articles were included in this meta-analysis. The Spearman correlation coefficient was 0.114, p = 0.739, and the SROC curve did not show a “shoulder-arm” shape, which suggests that there was no threshold effect, but study heterogeneity existed because of non-threshold effects. The combined sensitivity was 0.72 [95% confidence interval (CI): 0.65–0.78], specificity was 0.65 (95% CI: 0.45–0.81), PLR was 1.75 (95% CI: 1.33–2.31), NLR was 0.48 (95% CI: 0.37–0.63), DOR was 3.63 (95% CI: 2.29–5.74), and AUC was 0.75. The Deeks' test suggested no significant publication bias in the included studies (P = 0.94). Conclusion: sST has some diagnostic value in HF, but this should be further evaluated in additional studies with rigorous design and high homogeneity.